Aplikasi Manajemen Risiko pada Pembangunan Sistem Penyediaan Air Minum (SPAM) Regional Jawa Tengah (Studi Kasus pada Pembangunan Jaringan Transmisi SPAM Regional Bregas) - Septiani, Hernoni; Wibowo, M. Agung; Syafrudin, Syafrudin (Department of Civil Engineering, Diponegoro University, 2015)
The increasing need for drinking water and undistributed raw water source needs solution with SPAM, Central Java Region. One of it is SPAM Bregas Region which the service locations are in Brebes Districts, Tegal City, and Tegal District. In the process of the transmission network development, there come some risks that hamper so that it needs for further research. This research aims to identify risks, analyze the amount of risk probability and give policy recommendations. The responden of study are government agencies as providers the transmission pipelines development projects of Bregas Regional SPAM, also the supervision consultants and contractors as a service providers. The method used is to spread the questionnaire to each stakeholder for structuring the risk of using RBS (Risk Breakdown Structure) and multiplying the value of the impact and frequency to obtain the value of the level of risk for each risk factor. The results showed the risks that happened in transmission network development in Bregas Regional SPAM are different from each stakeholder. Risks from perception of the supervising consultant 21.95% is accepted, 18.29% mitigated, and 59.76% avoided. Risk from owner perseption 32.93% is accepted, 23.17% mitigated, and 43.90% avoided. Rizks from contractor perseption 23.17% is accepted, 29.27 mitigated, and 47.56% avoided. Overall stakeholder’s biggest risk is land acquisition.